Interventional oncology and immunotherapy: current status and future perspectives - Ma, Ji; Wei, Zhigang; Ye, Xin (Frontiers in Immunology, 2025)
Interventional oncology has become an important part of multidisciplinary cancer treatment following the development of interventional radiology. Tumors can release antigens, activate immunity, and cause an abscopal effect after interventional therapy. However, the activated immune response is limited and involves a complex process. New methods to solve the problems were developed following the advent of immunotherapy. The combination therapies enhanced the antitumor immune response and improved patient outcomes with good application prospects. In this review, we have summarized the interventional therapies used to improve immune efficacy and discussed the advancements in combining interventional therapy and immunotherapy.